Child care and health rights: perspectives of adolescent mothers - Jaqueline Silva Santos; Raquel Dully Andrade; Juliana Coelho Pina; Maria de La Ó Ramallo Veríssimo; Anna Maria Chiesa; Débora Falleiros de Mello (SciELO, 2015)
AbstractOBJECTIVETo analyze child health care and the defense of their rights from the perspective of adolescent mothers.METHODSAn exploratory study with qualitative thematic analysis of data, based on conceptual aspects of care and the right to health, from semi-structured interviews with 20 adolescent mothers ascribed by Family Health teams.RESULTSMaternal reports indicate that child health care requires responsibility and protection, with health practices that promote child advocacy. Gaps in assistance which preclude the full guarantee of the right to child health care were also highlighted.CONCLUSIONThe right to health care assumed different meanings, and the forms to guarantee them were linked to individual behavior in detriment to broader actions that consider health as a social product, connected to the guarantee of other fundamental rights.